2012
DOI: 10.1016/j.bpj.2012.04.040
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Feedback Model for Adaptation in the Olfactory Transduction Pathway

Abstract: Olfactory transduction exhibits two distinct types of adaptation, which we denote multipulse and step adaptation. In terms of measured transduction current, multipulse adaptation appears as a decrease in the amplitude of the second of two consecutive responses when the olfactory neuron is stimulated with two brief pulses.Step adaptation occurs in response to a sustained steplike stimulation and is characterized by a return to a steady-state current amplitude close to the prestimulus value, after a transient pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Refs. 33 and Supplementary Figure 8 of De Palo et al17). This implies that feedback regulation is crucial for adaptation in our olfactory neurons.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Refs. 33 and Supplementary Figure 8 of De Palo et al17). This implies that feedback regulation is crucial for adaptation in our olfactory neurons.…”
Section: Discussionmentioning
confidence: 96%
“…17 we have observed that the two forms of adaptation mentioned so far, step adaptation and multipulse adaptation, appear to be in a dynamical trade-off: the more step adaptation gets closer to perfect, the slower is the recovery in multipulse adaptation and viceversa. The limiting case of perfect step adaptation corresponds to no recovery at all in multipulse adaptation.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…-binding factors such as Ca 2C -calmodulin, reduces the sensitivity of the channels to cAMP, a mechanism relevant for adaptation. [47][48][49][50][51][52] cAMP activates cationic CNG channels in the ciliary membrane and knockout mice missing the CNG channel subunit CNGA2 lacked electro-olfactogram (EOG) responses (which represent the recorded summated generator potential from the surface of the OE) 53,54 to most odorants tested. 55 The absence of EOG responses indicated that CNGA2 KO mice are anosmic.…”
Section: Camp-activated Currentsmentioning
confidence: 99%